Revolving-door Patients in Public Psychiatric Hospital in Israel: Cross Sectional Study - Oyffe, Igor (Croatian Medical Schools, 2009)
AIM: To study social, demographic, clinical, and forensic profiles of frequently re-hospitalized (revolving-door) psychiatric patients. METHODS: The study included all patients (n = 183) who were admitted to our hospital 3 or more times during a 2-year period from 1999 through 2000. We compared these patients to 2 control groups of patients who were admitted to our hospital in the same period. For comparison of forensic data, we compared them with all non revolving-door patients (n = 1056) registered in the computerized hospital database and for comparison of medical and clinical data we compared them with a random sample of non revolving-door patients (n = 98). The sample was sufficiently large to yield high statistical power (above 98%). We collected data on the legal status of the hospitalizations (voluntary or involuntary) and social, demographic, clinical, and forensic information from the forensic and medical records of revolving-door and non revolving-door patients. RESULTS: In the period 1999-2000, 183 revolving-door patients accounted for 771 (37.8%, 4.2 admissions per patient) and 1056 non revolving-door patients accounted for 1264 (62.5%, 1.2 admissions per patient) of the 2035 admissions to our hospital. Involuntary hospitalizations accounted for 23.9% of revolving-door and 76.0% of non revolving-door admissions. Revolving-door patients had significantly shorter mean interval between hospitalizations, showed less violence, and were usually discharged contrary to medical advice. We found no differences in sex, marital status, age, ethnicity, diagnoses, illegal drug and alcohol use, or previous suicide-attempts between the groups. CONCLUSIONS: Revolving-door patients are not necessarily hospitalized for longer time periods and do not have more involuntarily admissions. The main difference between revolving-door and non revolving-door patients is greater self-management of the hospitalization process by shortening the time between voluntary re-admission and discharge against medical advice.